2016
DOI: 10.1186/s13014-016-0596-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of oesophageal radiation dose volume metrics, neutropenia and acute radiation oesophagitis in patients receiving chemoradiotherapy for non-small cell lung cancer

Abstract: IntroductionThe relationship between oesophageal radiation dose volume metrics and dysphagia in patients having chemoradiation (CRT) for non-small cell lung cancer (NSCLC) is well established. There is also some evidence that neutropenia is a factor contributing to the severity of oesophagitis. We retrospectively analysed acute radiation oesophagitis (ARO) rates and severity in patients with NSCLC who received concurrent chemotherapy and high dose radiation therapy (CRT). We investigated if there was an associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…Although a greater proportion of patients with neutropaenia grade ≥2 developed grade ≥2 oesophagitis (80%) than patients who did not experience neutropaenia (38%), this was not statistically significant. However, it is not consistent with our previous study of oesophagitis and neutropaenia, and work by De Ruysscher et al (2007), where an association between these toxicities was observed . The lack of a statistically significant association in the current study is likely due to the small sample size of 40 patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although a greater proportion of patients with neutropaenia grade ≥2 developed grade ≥2 oesophagitis (80%) than patients who did not experience neutropaenia (38%), this was not statistically significant. However, it is not consistent with our previous study of oesophagitis and neutropaenia, and work by De Ruysscher et al (2007), where an association between these toxicities was observed . The lack of a statistically significant association in the current study is likely due to the small sample size of 40 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…(2016) reported no difference in O max between patients with G0 vs G ≥ 1 ARO, whereas we observed a significant difference in O max between G0–1 and G2–3 severity groups ( P = 0.0061). Our data reporting associations between radiation dose and ARO are consistent with previous studies by our own team and others; O max , O mean and the volume of oesophagus receiving ≥ 35 Gy were associated with clinically significant ARO …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Associations between radiation dose and clinically significant acute radiation esophagitis have been reported when the esophagus receives ≥35 Gy [ 9 , 11 ]. In addition to esophageal dose-volume metrics, neutropenia may also be a risk factor for higher grades of acute radiation esophagitis [ 12 ]. Both concurrent chemoradiotherapy (CRT) and the volume that receives at least 35 Gy are predictors of acute esophageal toxicity [ 13 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%